Adaptasi Beberapa Varietas Jagung pada Agroekosistem Lahan Kering di Maluku - Kaihatu, Sheny Sandra; Pesireron, Marietje (Jurnal Penelitian Pertanian Tanaman Pangan, 2016)
Maize has an important role in the national economy, but at some area, including in Maluku, the productivity is still low, below its potential productivity. The productivity of maize could be improved by planting high yielding and adaptive variety to the local environment. Study was conducted in the Haruru village, District Amahai, Central Maluku, from March to August 2012 aimed to identify maize varieties adaptive on dry land agro ecosystem. The study used randomized block design, replicated three times, where farmers’ fields were used as replications. The varieties tested were Srikandi Kuning, Gumarang, and Sukmaraga composites varieties. Bima-2 and Bima-2 (hybrid varieties) and Mutiara, Ungu Hati Putih, Merah, Orange Hati Putih, and Orange Hati Merah (local variety, obtained from farmers’ fields in the district of MTB). Fertilizers were drilled, 5-7 cm on the side of plant at a rate of 135 kg N, 90 kg P2O5, 60 kg K2O and 1-2 t manure/ha. Variables to be measured were percentage of surviving plants, age at 50% of male flowering, age at 50% of female flowering, plant height, ear height, cob length, cob weight, cob diameter, number of rows/ear, seed number per ear row, 100-seed weight, weight of dry grains, moisture content, and grain yield. Results showed that local varieties indicated a better growth, but grain yield were superior for the hybrid and the composite varieties. Bima-4 hybrid variety produced 10.31 t/ha dry grain, followed by Bima-2 hybrid and the composite varieties of Sukmaraga, Srikandi Kuning, and Gumarang, each was 8.70 t/ha, 7.97 t/ha, 7.60 t/ha and 7.26 t/ha, respectively. Local varieties Mutiara, Orange Hati Putih, Merah, Orange Hati Merah, and Ungu Hati Putih each yielded only 3.74 t/ha, 3.32 t/ha, 3.07 t/ha, 3.02 t/ha and 2.45 t/ha respectively.